Vessel Collision Avoidance System (VCAS) Based on AIS Data - Arinta Y. Wardani; A.A. Masroeri; Aulia S. Aisjah (Institut Teknologi Sepuluh Nopember, 2015)
In Indonesia, Maritime transportation delivers more than 71% of 96% to international trade in the world. It is a huge contribution to Indonesian economy. But, it is in contrary in the matter of safety. Based on National Transportation Safety Committee, there are 31 marine accidents, and around 25% of them is ship collisions which caused by human error. Accordingly, the research proposes a design of Vessel Collision Avoidance System (VCAS) based on AIS data as the input of vessel identification trajectory by using Fast Patrol Boat. As the result, this paper simulates Fast Patrol Boat maneuvering to prevent collision with another vessel.